2001
DOI: 10.1002/1521-379x(200111)53:11<570::aid-star570>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Physicochemical Properties of Acid-Thinned Corn, Potato and Rice Starches

Abstract: The structures and physicochemical properties of acid‐thinned corn, potato, and rice starches were investigated. Corn, potato, and rice starches were hydrolyzed with 0.14 N hydrochloric acid at 50 °C until reaching a target pasting peak of 200—300 Brabender Units (BU) at 10% solids in the Brabender Visco Amylograph. After acid modification the amylose content decreased slightly and all starches retained their native crystallinity pattern. Acid primarily attacked the amorphous regions within the starch granule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
115
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(156 citation statements)
references
References 13 publications
35
115
1
3
Order By: Relevance
“…The final viscosity of acid thinned modified starches was more than peak and hot paste viscosity. Acid modified starches show higher final viscosity supporting the fact that amylose terminated the short term gel structure development (Wang and Wang 2001). Kaur et al (2007) studied on the effect of aqueous HCl on properties of wheat starch and found that the pasting temperature, peak viscosity, hot paste viscosity and cold paste viscosity showed a decline with acid modification.…”
Section: Resultsmentioning
confidence: 95%
“…The final viscosity of acid thinned modified starches was more than peak and hot paste viscosity. Acid modified starches show higher final viscosity supporting the fact that amylose terminated the short term gel structure development (Wang and Wang 2001). Kaur et al (2007) studied on the effect of aqueous HCl on properties of wheat starch and found that the pasting temperature, peak viscosity, hot paste viscosity and cold paste viscosity showed a decline with acid modification.…”
Section: Resultsmentioning
confidence: 95%
“…The LGC of the acid hydrolysed and low-citric acid substituted starches improved from 4% (native) to 2% (Table 2) across cultivars, except for bitter yam starch. Acid hydrolysed hybrid maize starch, corn starch, potato, rice, red bean and cassava starches showed improved gelling capacity over their unmodified counterparts Wang and Wang 2001;Osunsami et al 1989;Kim and Ahn 1996). In our study, native and tempered starches developed soft viscous gels at lower concentrations (2-4% w/v), which became progressively hard or very hard as concentration increased (10-20% w/v), while acid hydrolysis and low-citric acid-substitution enhanced formation of hard gels at the different concentrations (2-20% w/v) in all cultivars.…”
Section: Least Gel Formation Concentration (Lgc) Of Native and Modifimentioning
confidence: 99%
“…The extent of hydrolysis depends on starch consistency, acidity of the medium, hydrolysis temperature, and duration of hydrolysis. The effects of acid hydrolysis of various starches, such as corn, potato, and rice, have been studied previously (Wang and Wang 2001;Wang et al 2003;Thirathumthavorn and Charoenrein 2005). Moreover, acid treatment in alcohol, especially for sago starch, has been conducted by Yiu et al (2008), and their study showed that sago starch can be modified through hydrolysis and alcoholysis to give various limit dextrins with high solubility.…”
Section: Slow Acid Hydrolysismentioning
confidence: 99%